Sistem Pendukung Keputusan Penyaluran Program Bantuan Pangan Non Tunai (BPNT) Metode Simple Additive Weighting (SAW) Di Kelurahan Brudu Kecamatan Sumobito Kabupaten Jombang - Rizal, Fatchur; Imam Agung, Achmad; Augusta Jannatul Firdaus, Reza (Inovate, 2021)
Because poverty is the highlight of one of the economic problems that exist in various countries and even the world and including this country, and the poverty rate is a multidimensional problem. This assistance program is part of the poverty reduction program of the government in the first cluster, namely activities on social protection based on the head of the family in meeting or determining the basic food needs of the less fortunate. This food aid will be distributed to the respective officers who take care of the regency or city in the form of non-cash or what is called in-kind, that is, the assistance will be provided in the form of rice and or eggs that have been provided by agents in each region. This study aims to design or create a decision support system for beneficiaries in Brudu village and to implement a decision support system using the Simple Additive Weighting (SAW) method, which is a method for determining aid distribution. The results of this research are managing data of potential beneficiaries with weighted calculations in order to help Brudu Village, Sumobito District, Jombang Regency, namely by using and implementing a system that is more able to work quickly to get results, is appropriate in assessment, and objectively in a decision making so that the selection produced and issued in these results are valid and truly it can be said to be valid that the community deserves assistance and the level of valid data accuracy in the system for determining non-cash food aid using the Simple Additive Weighting (SAW) method is 83.851% Keywords:Non-cash Food Aid Distribution System, Information System, SAW, Action Research, Website